The effect of induced polyploidy on phytochemistry, cellular organelles and the expression of genes involved in thymol and carvacrol biosynthetic pathway in thyme (Thymus vulgaris) - Mohammadi, Valiollah; Talebi, Samaneh; Ahmadnasab, Masoumeh; Mollahassanzadeh, Hossein (Frontiers in Plant Science, 2023)
Induced polyploidy usually results in larger vegetative and reproductive plant organs. In order to study the effect of chromosome doubling on Thymus vulgaris, three levels of colchicine concentration including 0.1, 0.3 and 0.5 % (w/v) were applied for 6, 12 and 24 hours on apical meristem of 2-and 4-leaf seedlings. Ploidy level was evaluated by flow cytometry and microscopic chromosome counting. Chemical composition of essential oils extracted by hydro-distillation was analyzed by gas Chromatography/mass spectrometry (GC/MS) and gas Chromatography (GC). The application of 0.3% colchicine at 4-leaf seedling for 6 hours resulted in the highest survival rate and the highest number of tetraploid plants. Cytogenetic and flow cytometry analyses confirmed the increase of chromosome number from 2n=2x=30 in diploids to 2n=4x=60 in induced tetraploids.Tetraploid plants had larger leaves, taller and thicker stems, dense branching, longer trichome, larger stomata, larger guard cells, and decreased number of stomata. The number of chloroplasts and mitochondria increased significantly in tetraploid plants by 1.66 and 1.63 times, respectively. The expression of CYP71D178, CYP71D180 and CYP71D181 increased in tetraploids by 3.27, 7.39 and 2.15 times, respectively, probably resulting in higher essential oil compounds, as tetraploids outyielded the diploid plants by 64.7% in essential oil, 40.9% in thymol and 18.6% in carvacrol content.